Ocean Species Discoveries 1–12 — A primer for accelerating marine invertebrate taxonomy - (SOSA), Senckenberg Ocean Species Alliance; Brandt, Angelika; Chen, Chong; Engel, Laura; Esquete, Patricia; Horton, Tammy; Jażdżewska, Anna; Johannsen, Nele; Kaiser, Stefanie; Kihara, Terue; Knauber, Henry; Kniesz, Katharina; et al. (Biodiversity data journal, 2024)
Discoveries of new species often depend on one or a few specimens, leading to delays as researchers wait for additional context, sometimes for decades. There is currently little professional incentive for a single expert to publish a stand-alone species description. Additionally, while many journals accept taxonomic descriptions, even specialist journals expect insights beyond the descriptive work itself. The combination of these factors exacerbates the issue that only a small fraction of marine species are known and new discoveries are described at a slow pace, while they face increasing threats from accelerating global change. To tackle this challenge, this first compilation of Ocean Species Discoveries (OSD) presents a new collaborative framework to accelerate the description and naming of marine invertebrate taxa that can be extended across all phyla. Through a mode of publication that can be speedy, taxonomy-focused and generate higher citation rates, OSD aims to create an attractive home for single species descriptions. This Senckenberg Ocean Species Alliance (SOSA) approach emphasises thorough, but compact species descriptions and diagnoses, with supporting illustrations and with molecular data when available. Even basic species descriptions carry key data for distributions and ecological interactions (e.g., host-parasite relationships) besides universally valid species names; these are essential for downstream uses, such as conservation assessments and communicating biodiversity to the broader public. This paper presents thirteen marine invertebrate taxa, comprising one new genus, eleven new species and one re-description and reinstatement, covering wide taxonomic, geographic, bathymetric and ecological ranges. The taxa addressed herein span three phyla (Mollusca, Arthropoda, Echinodermata), five classes, eight orders and twelve families. Apart from the new genus, an updated generic diagnosis is provided for four other genera. The newly-described species of the phylum Mollusca are Placiphorella methanophila Vončina, sp. nov. (Polyplacophora, Mopaliidae), Lepetodrilus marianae Chen, Watanabe & Tsuda, sp. nov. (Gastropoda, Lepetodrilidae), Shinkailepas gigas Chen, Watanabe & Tsuda, sp. nov. (Gastropoda, Phenacolepadidae) and Lyonsiella illaesa Machado & Sigwart, sp. nov. (Bivalvia, Lyonsiellidae). The new taxa of the phylum Arthropoda are all members of the subphylum Crustacea: Lepechinella naces Lörz & Engel, sp. nov. (Amphipoda, Lepechinellidae), Cuniculomaera grata Tandberg & Jażdżewska, gen. et sp. nov. (Amphipoda, Maeridae), Pseudionella pumulaensis Williams & Landschoff, sp. nov. (Isopoda, Bopyridae), Mastigoniscus minimus Wenz, Knauber & Riehl, sp. nov. (Isopoda, Haploniscidae), Macrostylis papandreas Jonannsen, Riehl & Brandt, sp. nov. (Isopoda, Macrostylidae), Austroniscus indobathyasellus Kaiser, Kniesz & Kihara, sp. nov. (Isopoda, Nannoniscidae) and Apseudopsis daria Esquete & Tato, sp. nov. (Tanaidacea, Apseudidae). In the phylum Echinodermata, the reinstated species is Psychropotes buglossa E. Perrier, 1886 (Holothuroidea, Psychropotidae). The study areas span the North and Central Atlantic Ocean, the Indian Ocean and the North, East and West Pacific Ocean and depths from 5.2 m to 7081 m. Specimens of eleven free-living and one parasite species were collected from habitats ranging from an estuary to deep-sea trenches. The species were illustrated with photographs, line drawings, micro-computed tomography, confocal laser scanning microscopy and scanning electron microscopy images. Molecular data are included for nine species and four species include a molecular diagnosis in addition to their morphological diagnosis. The five new geographic and bathymetric distribution records comprise Lepechinella naces Lörz & Engel, sp. nov. , Cuniculomaera grata Tandberg & Jażdżewska, sp. nov. , Pseudionella pumulaensis Williams & Landschoff, sp. nov. , Austroniscus indobathyasellus Kaiser, Kniesz & Kihara, sp. nov. and Psychropotes buglossa E. Perrier, 1886, with the novelty spanning from the species to the family level. The new parasite record is Pseudionella pumulaensis Williams & Landschoff, sp. nov. , found in association with the hermit crab Pagurus fraserorum Landschoff & Komai, 2018.